Investigación de operaciones en la ciencia administrativa - EPPEN, G.D.; GOULD, F.J.; SCHMIDT, C.P.; MOORE, Jeffrey H.; WEATHERFORD, Larry R. (PRENTICE-HALL LATINOAMERICANA, 2000)
Contiene: 1 CD/R del Libro.